Juventude e escola: dialÃgos sobre a relaÃÃo com o saber e O Programa NÃcleo De Trabalho, Pesquisa e PrÃticas Sociais - Klertianny Teixeira do Carmo (2017)
The present research has as a theme the relationship between knowledge and Education in the secondary school, and as an object of the research, the significance and the proposal sense of the curricular reformulation called of the NÃcleo de Trabalho, Pesquisa e PrÃticas Sociais (NTPPS) for the young people at two secondary schools. This proposal is functioning since 2012 in the CearÃ state (Brazil), search to reframe of the school, the knowledge and the learning from the development of socio-emotional skills using the research as a pedagogical tool and stimulating the development of life and career projects. Since many educational approaches do not accompany contemporary changes, insisting in the not recognizing the young people as active subjects in the construction of school space, thus contributing to the lack of meaning to what is taught. Preclude the mobilization of the young person to learn, thus contributing to the school failure. Therefore, a dialogue about the relationship with the knowledge built in that program is extremely relevant for understanding the meaning that young people attribute to school. Thus, our central inquiry is knows how the experience in the NTPPS program can contribute to a change in the relationship between the learning of the youth. In the search of the get an answer this issue, this study has the main goal to understand how the experience in the NTPPS program can contribute to a change in the relationship with the learning of the young people in the school context. And as specific goals: A) Reveal the knowledge that is created by students with and in NTPPS; B) Reveal the relationship of youth with and in research and C) Propose reflections that enhance think about the secondary school as the "youth face" by means their contribution. Were used as theoretical references the studies about critical education (FREIRE, 1987, 2006, 2014); relation with the knowledge (CHARLOT, 2000; 2001; 2013). A research with the qualitative approach (BOGDAN; BIKLEN, 1994) of the descriptive and exploratory content. The participant subject/authors of the research were 27 youth, from the second year of secondary school, which developed research projects, in 2016, focused on the macro sports or leisure field and five teachers from the NTPPS, at two public schools in Fortaleza-CE. The method of research used was the Paradigma IndiciÃrio (GINZURG; 1989). The techniques of data collecting the data were: observation participant (CHIZZOTTI, 1995) of the classes of NTPPS; individual interview (GASKELL, 2007) with teachers; group interview with young people, based on conference using photos, drawings, and letters. The analyses of data were realized following the methods of Bardin (2011) and Gemma Penn (2007). The results of this research showed that this proposal for reformulation brought advances in the relationship with the knowledge of young people producing other forms of more meaningful learning within the school, respecting the knowledge brought by young people, regarding the choice by research themes of their interest ; the need to improve relationships with you and with others; as well as in the learning of investigative techniques and instruments helping in life, contemplating the legal objectives of this teaching. However, it brings with it some structural obstacles to school organization that still prevent its greater effectiveness when